Effects of various management control measures on seasonal leaf quality of colophospermum mopane and tragelaphus strepsiceros browse of C. mopane, Limpopo Province, South Africa - Makhado, Rudzani Albert (My University, 2020)
Colophospermum mopane (Benth.) J. Léonard, commonly known as mopane, is a dominant tree or shrub in the mopane woodland. It is distributed in the low-lying areas of southern Africa’s savannas. Mopane maintains its foliage well into the dry season, and thus provides nutritional forage for browsers such as Tragelaphus strepsiceros, commonly known as the greater kudu. Despite its wide distribution and value as a source of forage for browsers, especially during the dry season, knowledge of the effect of browsers on mopane leaf quality is limited. There is also inadequate knowledge of the diet composition of the greater kudu during different seasons in the mopane woodland. Such information is important for proper management of browsers in the mopane woodland. As a result, a field experiment was conducted at Musina Nature Reserve, Limpopo Province, South Africa to determine the effect of pruning on mopane leaf phenology, production, macronutrients, trace elements and secondary metabolites. Pruning was conducted to simulate the effect of browsing by large herbivores such as the greater kudu on mopane leaf quality. In addition, rumen content analysis of greater kudu was conducted in order to quantify the amount of mopane and other plants browsed during the dry and wet seasons. Collected datasets were analysed using descriptive and inferential statistics. A two-tailed Mann-Whitney U-test was used to test the effect of pruning on mopane leaf phenology and production. The effect of pruning on the monthly concentration of macronutrients, trace elements and secondary metabolites was tested using a two-tailed t-Test: Two-Sample Assuming Equal Variance. The seasonal and annual effect of pruning on the concentration of macronutrients, trace elements and secondary metabolites was tested using One-Way Anova. Rumen datasets were analysed using the Pearson Correlation Coefficient. This study found that the rate of leaf phenology and production, including the concentration of certain macronutrients (Ca, K, N, P, S, Cl, Na, protein and fibre), trace elements (Fe, Mn, Mo, Cu, Zn and Se) and secondary metabolites (TP, CT and PPT) increased during leaf flush in October and then declined as the leaves ii matured and aged. However, the concentration of selected macronutrients (Mg and NO3) and trace elements (B, Co and F) increased when the leaves reached maturity in June, particularly during the leaf senescence stage, and declined thereafter. The concentration of macronutrients, trace elements and secondary metabolites between the control and pruned trees was statistically insignificant at P>0.05 for most samples. This study further showed that C. mopane contributed most (47%) to the diet of the greater kudu during the dry season. Other important dry season browse plants were Dichrostachys cinerea (30%), Commiphora edulis (12%), Grewia bicolor (6%) and Combretum apiculatum (5%). However, when gender was considered, the diet of the female greater kudu during the dry season consisted mainly of C. mopane (71%) and D. cinerea (22%). The diet of the male greater kudu contained less C. mopane (33%), but similar proportions of D. cinerea (31%) and other browse species. However, during the wet season, the diet of the greater kudu was mainly composed of C. apiculatum (43%). Other wet season browse plant species were Sclerocarya birrea (24%), C. mopane (12%) and Senegalia nigrescens (8%), with the contribution of the remaining species to the diet being insignificant. The diet of the female greater kudu in the wet season consisted mainly of C. apiculatum (44%) and C. mopane (20%), while the diet of the male mostly contained S. birrea (38%) and C. apiculatum (34%). It is concluded that the concentration of macronutrients, trace elements and secondary metabolites in mopane leaves is not dependent on <10% pruning, but seems to be associated with leaf growth stages. It is further concluded that the concentration of nutrients and chemical compound in mopane leaves has implications on the diet composition of browsers such as the greater kudu in the mopane woodland. The dependency of the greater kudu on species such as C. mopane and C. apiculatum as main sources of browse indicates the importance of these species to the diet of the greater kudu in the mopane woodland.
Thesis (Ph. D. (Botany)) -- University of Limpopo, 2020
Keywords: Colophosperimum mopane; Woodland mopane; Mopane tree; Mopane worms